2014
DOI: 10.4049/jimmunol.1300039
|View full text |Cite
|
Sign up to set email alerts
|

Conventional NK Cells Can Produce IL-22 and Promote Host Defense in Klebsiella pneumoniae Pneumonia

Abstract: It has been reported that host defense against pulmonary K. pneumoniae infection requires IL-22, which has been proposed to be of T cell origin. Supporting a role for IL-22, we found that Il22−/− mice had decreased survival as compared with wild type mice after intratracheal infection with K. pneumoniae. Surprisingly, however, Rag2−/− mice did not differ from wild type mice in survival or levels of IL-22 in the lungs after infection with K. pneumoniae. By contrast, K. pneumoniae-infected Rag2−/−Il2rg−/− mice f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 69 publications
1
62
3
2
Order By: Relevance
“…The combination of IL-22 with IL-17 also induced several pro-inflammatory cytokines and chemokines or antimicrobial peptides expression in lung epithelial cells [10]. Another study also found that, comparing with wild-type mice, Il22-deficient mice died quickly after Klebsiella pneumoniae infection [301]. As described above, after Citrobacter rodentium infection, deficiency of IL-22 in mice led to increased intestinal damage, bacterial load and mortality [325].…”
Section: Th17 Effector Cytokines In Host Defense Against Infectionmentioning
confidence: 82%
“…The combination of IL-22 with IL-17 also induced several pro-inflammatory cytokines and chemokines or antimicrobial peptides expression in lung epithelial cells [10]. Another study also found that, comparing with wild-type mice, Il22-deficient mice died quickly after Klebsiella pneumoniae infection [301]. As described above, after Citrobacter rodentium infection, deficiency of IL-22 in mice led to increased intestinal damage, bacterial load and mortality [325].…”
Section: Th17 Effector Cytokines In Host Defense Against Infectionmentioning
confidence: 82%
“…Both Th17 and Th22 cells were initially thought to be the origin of IL-22 during K. pneumoniae infection (184). However, since recent work has shown that ␣␤ T cells are unnecessary for the control of infection (184), while NK cells both promote the survival of mice during K. pneumoniae pneumonia and produce IL-22 (189), it is now thought that NK cells are the major source of IL-22 and are critical for controlling K. pneumoniae infections in lungs. Another innate lymphoid cell type, mucosa-associated invariant T (MAIT) cells, has also been suggested to play a nonredundant role in controlling infection, particularly in the K. pneumoniae peritonitis model (184,190,191).…”
Section: K Pneumoniae and Host Immune Defensesmentioning
confidence: 99%
“…Similarly, CD8 + T cells have been shown to provide resilience in response to influenza and RSV infections, as sources of IL-10, which curbs lung injury (119); such roles of CD8 + T cells outside of viral infection remain less certain. NK cells are sources of IL-22 and its contributions to resilience during K. pneumoniae or influenza pneumonia (100, 120). A novel set of tissue-protective lymphocytes was identified during influenza infection as a population of lineage-negative CD90 + CD25 + innate lymphoid cells that promote resilience through expression of the EGF family member amphiregulin (121).…”
Section: Resilience: Tissue-protective Pathways Countering Lung Injurymentioning
confidence: 99%